Damage observation in glass fiber reinforced composites via μ-tomography. (2019) - Tomičević, Zvonimir; Bouterf, Amine; Surma, Robert; Hild, François
Abstract: The present study deals with a three dimensional analysis of a cyclic uniaxial experiment on a glass fibre reinforced epoxy resin composite. From monotonic and cyclic uniaxial mechanical experiments and by using a 2D digital image correlation optical setup, the macroscopic material behaviour is revealed. Based on the observed response, an ex situ cyclic tomography experiment was defined and conducted. The investigated dog-bone sample was loaded at four different load levels. At each subsequent unloaded stage, the sample was scanned in a laboratory tomograph. The 3D reconstructed volumes were analyzed with FE-based digital volume correlation in order to measure displacement fields in the region of interest. Since very low permanent strains were reported, the gray level correlation residuals were studied to observe the damaged zones in the bulk of the sample. Overlaying the correlation residuals with the corresponding microstructure accurately depicts damage mechanisms occurring in the investigated material.